The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1161/circimaging.113.001420
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights and Characterization of Sickle Cell Disease–Associated Cardiomyopathy

Abstract: Background Cardiovascular disease is an important cause of morbidity and mortality in sickle cell disease (SCD). We sought to characterize sickle cell cardiomyopathy using multi-modality non-invasive cardiovascular testing and identify potential causative mechanisms. Methods and Results Stable adults with SCD (n=38) and healthy controls (n=13) prospectively underwent same day multi-parametric cardiovascular magnetic resonance (cine, T2* iron, vasodilator first pass myocardial perfusion, and late gadolinium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 21 publications
3
77
2
2
Order By: Relevance
“…Thus, LVED enlargement and LVH were more noticeable in meta-analysis results, compared to our data from a younger cohort of SCD patients than most studies in the meta-analysis. A recent publication described 4-chamber dilation, normal systolic function and diastolic dysfunction in adults with SCD(31) that contrasts with our data in a much younger cohort with milder anemia. With increasing age, LV dilation and LVH are expected to worsen, resulting in progressive 4-chamber dilatation.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, LVED enlargement and LVH were more noticeable in meta-analysis results, compared to our data from a younger cohort of SCD patients than most studies in the meta-analysis. A recent publication described 4-chamber dilation, normal systolic function and diastolic dysfunction in adults with SCD(31) that contrasts with our data in a much younger cohort with milder anemia. With increasing age, LV dilation and LVH are expected to worsen, resulting in progressive 4-chamber dilatation.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been recently reported that some degree of focal LV fibrosis measured using late gadolinium enhancement can be seen in young adults with SCA by CMR (42,48), and LV fibrosis was also reported in autopsies of young adults with SCA who died suddenly (77). Moreover, recent reports suggest dysregulated profibrotic pathways are up-regulated in SCA in general, as polymorphisms in TGF-β signaling pathway genes have been found in this patient population (78).…”
Section: Berk-ss Mice Develop Corrected Qt Prolongation and Widening supporting
confidence: 56%
“…This was associated with improved left ventricular outflow tract dimensions, suggesting a possible contribution of FD in delaying the progression of SCD cardiovascular disease. [54][55][56] We demonstrated a synergistic effect of ω-3 PUFA on both ET-1-mediated endothelial dysfunction and VCAM-1-mediated endothelial activation on aortas following H/R ( Figure 6A). Notably, FD also significantly reduced VCAM-1 expression in livers of SS mice exposed to H/R stress compared to the expression in SS-SD mice ( Figure 5).…”
Section: Discussionmentioning
confidence: 89%